Wunderkammer as critical communication pedagogy: Collaboratively documenting pedagogical labor in a cabinet of curiosities. Issue 3 (2nd July 2020) - Huber, Aubrey A.
Abstract : In this semester-long activity, I describe how to create a collaborative cabinet of curiosities that engages critical methods of inquiry as an alternative summative assignment. Courses: Communication Pedagogy, Gender and Communication, Performance Studies. Objective: The objective of this assignment is for students to identify and analyze how communication constitutes their educational experience.